ELEMENTARY MATHEMATICS EDUCATION OF PRESCHOOL CHILDREN IN THE UKRAINIAN HIGHLANDS - Ruslana Romanyshyn (Vasyl Stefanyk Precarpathian National University, 2015)
The paper highlights the challenges of establishment and characteristics of educational institutions functioning in the highlands. It is analyzed the work of preparatory groups that are meant to replace kindergartens in the remote mountainous areas in terms of preparing children for school. In the context of logical and mathematical development of senior preschool children we analyze the Program "Sure Start" and the issue of elementary mathematics education. It is concluded that the acquisition of this knowledge in preschool institutions and preparatory groups affects the quality of further mathematics education. In this regard effective solution to the implementation of the tasks of the Program "Sure Start" in mountainous regions is seen in cooperation on the part of kindergartens, schools and parents.